Prosedur Pelayanan Terhadap Kepuasan Pelanggan Pada Indomaret Tugu Cimanggis - Rita Wahyuni (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This final report discusses the procedure of service to customer satisfaction at Indomaret Tugu Cimanggis, by doing observation and interview to Indomaret employee and compare it with theory that discuss about service procedure to customer satisfaction. Based on the observations that the author has done this aims to improve service to customer satisfaction Indomaret Tugu Cimanggis. Although there are still many problems encountered, but the problems faced are not too significant so only need a little evaluation to further improve the service to customer satisfaction. The data used are primary data collected and interview to Indomaret Tugu Cimanngis.